Implikasi Hukum atas Terjadinya Wanprestasi dalam Pelaksanaan Perjanjian Kerja Sama (Studi Kasus Jefri Nichol Vs Falcon Pictures) - Listiana, Sabrina Novi Putri; Nabillah, Farrah; Aulia, Najwa Nabila; Ilyasa, Muhammad Diaz; Sulastri, Sulastri (Media Hukum Indonesia (MHI), 2024)
This study aims to analyze the legal implications arising from default in the implementation of a cooperation agreement, with a case study of the dispute between Jefri Nichol and Falcon Pictures. This case attracted public attention because it involved a famous actor and a well-known production house in Indonesia, and contained various aspects of civil law that are relevant to the protection of the rights and obligations of the parties in the cooperation agreement. The approach used in this study is normative juridical supported by case studies. Data were collected through analysis of legal texts, regulations, contracts, and court decisions relevant to disputes over default in employment contracts. This study found that default in a cooperation agreement can trigger legal consequences, including compensation, cancellation of the agreement, or termination of the cooperation relationship. In the case of Jefri Nichol vs. Falcon Pictures, the main factor causing the dispute was a violation of the contract clause governing the exclusivity of the cooperation, which led to a lawsuit by Falcon Pictures against Jefri Nichol. The results of the study indicate that clear, detailed, and fair contract clause arrangements are very important to avoid legal disputes. In addition, settlement through mediation can be a more efficient alternative compared to litigation. This study provides recommendations to the parties involved in the cooperation agreement to improve their understanding of contract law and draft the agreement carefully by considering potential legal risks.